Structural capacity of reinforced concrete columns with U-shaped transverse bars. (1st August 2020) - Hwang, Hyeon-Jong; Noh, Ju-Ok; Park, Hong-Gun
Highlights: New transverse reinforcement detail for better constructability of large columns. Assembled U-shaped tie bars replacing conventional hoops and cross-ties. Compression loading test and cyclic lateral loading test of RC columns. Comparison of structural performance between the columns with the proposed details and conventional hoops and ties. Abstract: In large reinforced concrete (RC) columns for mega columns in high-rise buildings and plants, constructability is deteriorated due to difficulties in assembling long reinforcing bars. In the present study, U-shaped tie bars were studied to improve the constructability of large RC columns by replacing the hoops and cross ties with U-shaped tie bars. The compression loading test and cyclic lateral loading test were performed on RC columns to verify the effect of U-tie bars. For the test parameters, the types of U-tie bars, neutral axis depth of cross-section, and loading types were considered. The test results showed that the strength and deformation capacities of the columns using U-tie bars were comparable to those of the columns using conventional transverse reinforcement. Closely-spaced U-tie bars satisfactorily restrained early local buckling of the longitudinal bars and provided adequate confinement effect to the core concrete, without early failure of the U-bars. Further, design recommendations were discussed to use U-tie bars for transverse reinforcement in large columns.